Reversal of Systemic Hypertension-Associated Cardiac Remodeling in Chronic Pressure Overload Myocardium by Ciglitazone - Brooke C. Henderson, Utpal Sen, Corey Reynolds, Karni S. Moshal, Alexander Ovechkin, Neetu Tyagi, Ganesh K. Kartha, Walter E. Rodriguez, Suresh C. Tyagi (International Journal of Biological Sciences, 2007)
Elevated oxidative stress has been characterized in numerous disorders including systemic hypertension, arterial stiffness, left ventricular hypertrophy (LVH) and heart failure. The peroxisome proliferator activated receptor gamma (PPARγ) ameliorates oxidative stress and LVH. To test the hypothesis that PPARγ decreased LVH and cardiac fibrosis in chronic pressure overload, in part, by increasing SOD, eNOS and elastin and decreasing NOX4, MMP and collagen synthesis and degradation, chronic pressure overload analogous to systemic hypertension was created in C57BL/6J mice by occluding the abdominal aorta above the kidneys (aortic stenosis-AS). The sham surgery was used as controls. Ciglitazone (CZ, a PPARγ agonist, 4 µg/ml) was administered in drinking water. LV function was measured by M-Mode Echocardiography. We found that PPARγ protein levels were increased by CZ. NOX-4 expression was increased by pressure-overload and such an increase was attenuated by CZ. SOD expression was not affected by CZ. Expression of iNOS was induced by pressure-overload, and such an increase was inhibited by CZ. Protein levels for MMP2, MMP-9, MMP-13 were induced and TIMP levels were decreased by pressure-overload. The CZ mitigated these levels. Collagen synthesis was increased and elastin levels were decreased by pressure-overload and CZ ameliorated these changes. Histochemistry showed that CZ inhibited interstitial and perivascular fibrosis. Echocardiography showed that CZ attenuated the systolic and diastolic LV dysfunction induced by pressure-overload. These observations suggested that CZ inhibited pressure-overlaod-induced cardiac remodeling, and inhibition of an induction of NOX4, iNOS, MMP-2/MMP-13 expression and collagen synthesis/degradation may play a role in pressure-overload induced cardiac remodeling.